Effectiveness of the bowel management program in children with constipation secondary to anorectal malformations - Santos Jasso Karla A.; Ruiz Montañez Alejandro (Instituto Nacional de Pediatría, 2014)
Introduction: One thousand children with anorectal malformation (ARM) are born in Mexico every year. In spite of surgical correction, these children continue to present functional fecal problems (constipation and fecal incontinence). We conducted an Intestinal Rehabilitation Program (IRP) which consists of an initial rectal disimpaction followed by administration of stimulant-type laxative (senna), with favorable results. The objective of this paper is to describe the effectiveness of the Intestinal Rehabilitation Program/bowel management program (IRP/BMP) in children with constipation secondary to surgically corrected ARM. Materials and methods: A descriptive, retrospective, cross-sectional study, describing which was the IRP effectiveness in children with constipation secondary to ARM. The effectiveness was measured by means of a construct of three variables (presence of daily bowel movements, absence of fecal staining, and having a plain abdominal radiograph without fecal residue in left colon and rectum after passing stool). All children who had surgically corrected ARM and constipation in two referral centers were included. Results. One hundred and fifty one children with ARM were included: 21.85% had fecal incontinence, and 67.33% had constipation. Of this group 88.1% showed good response to the BMP. The mean dose of sennoside was 8.45 mg/kg, 95% CI: 5.94-11.12 mg/kg (199.5 mg total dose, 95% CI: 139.50-259.50 mg). Colicky abdominal pain occurred in 5.8% of the patients. Discussion. The use of sennoside has had a positive impact on our patients by means of colonic and rectal emptying without fecal soiling. Key words: Constipation, Anorrectal Malformation, Bowel Managment Program, Sennoside.